Association of foetal size and sex with porcine foeto-maternal interface integrin expression. Issue 4 (April 2019) - Stenhouse, Claire; Hogg, Charis O; Ashworth, Cheryl J
Abstract : Integrins regulate adhesion at the foeto-maternal interface by interacting with secreted phosphoprotein 1 (SPP1) and fibronectin (FN). It is hypothesised that impaired foetal growth of 'runt' piglets is linked to altered integrin signalling at the foeto-maternal interface. Placental and endometrial samples associated with the lightest and closest to mean litter weight (CTMLW) (gestational day (GD18, 30, 45, 60 and 90), of both sex (GD30, 45, 60 and 90) ( n  = 5–8 litters/GD), Large White × Landrace conceptuses or foetuses were obtained. The mRNA expression of the integrin subunits (ITG) ITGA2, ITGAV, ITGB1, ITGB3, ITGB5, ITGB6, ITGB8, SPP1 and FN was quantified by qPCR. Temporal changes in mRNA expression were observed, with different profiles in the two tissues. Endometrial ITGB1 ( P  ≤ 0.05, GD45) and SPP1 ( P  ≤ 0.05, all GD combined and GD60) expression was decreased in samples supplying the lightest compared to the CTMLW foetuses. Placentas supplying female foetuses had decreased expression of ITGB6 (GD45, P  ≤ 0.05) and FN (GD90, P  ≤ 0.05) compared to those supplying male foetuses. Endometrial samples supplying females had increased ITGB3 ( P  ≤ 0.05, GD60) and FN ( P  ≤ 0.05, GD30) expression and decreased SPP1 ( P  ≤ 0.05, GD60) expression compared to male foetuses. Correlations between mean within-gilt mRNA expression and percentage prenatal survival, number of live foetuses or conceptuses and percentage male foetuses were observed. This study has highlighted novel and dynamic associations between foetal size, sex and integrin subunit mRNA expression at the porcine foeto-maternal interface. Further studies should be performed to improve the understanding of the mechanisms behind these novel findings.